Low FXIII activity levels in patients with vascular anomalies, not in patients with trauma-induced coagulopathy - Hiroaki Otsubo; Tsuguaki Terashima; Mai Terashima; Siqiang Gao; Mika Ogawa; Hidefumi Kato; Kyosuke Takeshita; Shohei Mizuno; Satsuki Murakami; Akiyoshi Takakmi; Katsuhiko Matsuyama; Hiroshi Furukawa; et al. (PLoS ONE, 2026)
Patients with localized intravascular coagulopathy (LIC) related to vascular anomalies occasionally suffer from hemorrhage and delayed wound healing, presumably due to consumptive reduction of fibrinogen and platelets. However, LIC patients with normal levels of platelets and fibrinogen can be hemorrhagic for unknown reasons. These facts led us to hypothesize that factor XIII (FXIII) is decreased since FXIII plays an important role in hemostasis, tissue repair, and wound healing. We collected plasma from 17 patients with LIC (9 with aneurysm, 8 with vessel malformation) and 7 patients with trauma-induced coagulopathy (TIC), which showed a fibrinolytic phenotype similar to LIC, and measured FXIII levels. FXIII levels were considerably decreased (7–53%, mean 29.4%) in LIC patients. 13 of 17 patients showed bleeding tendency even though DIC scores were low. However, FXIII levels were only slightly decreased (39–98%, mean 67.4%) in TIC patients. We also investigated the correlation between FXIII activity and coagulation parameters. FXIII activity most strongly correlated with fibrinogen content (R = 0.882, P < 0.001) in LIC patients. FXIII levels below 50% were observed when fibrinogen was less than 200 mg/dL. Based on these findings, we successfully treated two LIC patients with FXIII concentrates. Decreased FXIII activity was specific to LIC, not TIC. Testing for FXIII activity should be considered in LIC patients even with normal fibrinogen levels, who are scheduled to undergo any invasive procedure, since FXIII supplementation is occasionally required for them.